THE STYLISTIC ROLE OF PERSONIFICATION IN ENGLISH LITERARY TEXTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines personification as a stylistic device, highlighting its role in attributing human emotions, qualities, and actions to inanimate objects, plants, or animals. The study emphasizes the importance of personification in children’s folklore, where it facilitates the understanding of natural phenomena, aids in language and logical thinking development, and teaches moral values. The article also discusses the linguistic origins of the term, its metaphorical function, and its presence in oral traditions, fairy tales, legends, ballads, and children’s literature. The findings demonstrate that personification is an effective educational and literary tool that enhances comprehension, imagination, and engagement in young audiences.